Dualisme Pertanggungjawaban Pidana dalam Kejahatan Prostitusi Online di Aceh - Riyan Auliyanda Safrizal; Hajrah Hajrah; Azzaril Ghafar; Raihan Putri; Fahmi Makraja (Universitas Palangka Raya, 2026)
This research aims to examine criminal liability for perpetrators of online prostitution in Aceh because the practice of online prostitution is currently carried out covertly because Aceh is a province that has special features in terms of implementing Islamic law, but in the practice of law enforcement against online prostitution crimes there are no regulations that can ensnare PSK, even though prostitutes are subjects who are directly involved in online prostitution crimes. This type of research uses an empirical juridical approach. The results of the research show that the regulation of the subject of offenses in online prostitution crimes is still not comprehensive, based on an investigation of norms, the regulatory focus in the Criminal Code is only on pimps and pimps, as well as in the ITE Law and the Pornography Law which focuses on social media content that can be disseminated, So there is no regulation that clearly states that commercial sex workers are the subject of offenses in conventional or online prostitution crimes. The handling of online prostitution cases carried out by wilayatul hisbah is by applying the ikhtilath and khalwath articles against perpetrators of online prostitution.